Long-term ecological studies in northern lakes – challenges, experiences, and accomplishments - Amundsen, Per-Arne; Primicerio, Raul; Smalås, Aslak; Henriksen, Eirik Haugstvedt; Knudsen, Rune; Kristoffersen, Roar; Klemetsen, Anders (Limnology and Oceanography, 2018)
Source at https://doi.org/10.1002/lno.10951 . We review three long‐term research programs performed over the last four decades on the ecology and management of oligotrophic lake systems with different fish communities at 69° N in Norway. Through whole‐lake perturbation experiments, intensive culling of stunted fish removed 35 tons (1984–1991) of Arctic charr Salvelinus alpinus in Takvatn (15 km 2 ) and 153 tons (1981–1983, 2002–2004) of European whitefish Coregonus lavaretus in Stuorajavri (25 km 2 ). In Takvatn, the overcrowded charr population decreased to 20% of the initial abundance, whereas brown trout Salmo trutta abundance increased. Somatic growth improved strongly in both species. In charr, ontogenetic habitat shifts broke down, the diet changed to more benthos, and plankton‐borne parasites decreased. High abundance of juvenile, littoral charr provided new prey for trout, creating an alternative, predator‐regulated stable state. Similar density reductions, positive effects on growth and reduced parasite loads occurred in whitefish in Stuorajavri. Despite the heavy culling, however, a new stable state did not occur and the fish community returned to the pre‐culling situation. In the Pasvik watercourse, vendace Coregonus albula invaded around 1990 after an upstream introduction. The population of this non‐native, highly specialized planktivore increased rapidly, resulting in steep density declines in zooplankton and the native planktivorous whitefish morph, and large changes in energy flow and structure and dynamics of the lacustrine food web. These programs show that long‐term research is essential for understanding the ecology of manmade disturbances and providing a scientific basis for management efforts.